Kegiatan Pemeriksaan Asam Urat Guna Mencegah Hiperurisemia Beserta Komplikasinya Pada Populasi Lanjut Usia Di Panti Werda Hana - Robert Kosasih; Junius Kurniawan; Kenzie Rafif Ramadhani; Muhammad Dzakwan (STIKes Ibnu Sina Ajibarang, 2024)
Serum uric acid (SUA) is the end product of purine metabolism in humans. When the body makes too much uric acid and the kidneys don't get rid of it quickly enough, this is called hyperuricemia. This leads to gouty arthritis because monosodium urate crystals build up in the joints. Normal SUA levels are 3.5–7.0 mg/dL in men and 2.6–6.0 mg/dL in women, influenced by diet, genetics, kidney function and medications. The prevalence of hyperuricemia is increasing globally, both in developed and developing countries. Although often asymptomatic, elevated SUA can cause tissue damage and increase the risk of hypertension, dyslipidemia, obesity, metabolic syndrome, type 2 diabetes, cardiovascular disease, and chronic kidney disease (CKD). This activity uses the PDCA (Plan-Do-Check-Action) method for early detection of hyperuricemia in the elderly at Hana Nursing Home, South Tangerang. Blood test results revealed hyperuricemia in 16 people (26.23%). Routine SUA screening helps identify individuals at risk and allows for preventive measures such as dietary changes and regular exercise.